Van de doofpot naar het kraambed : de holebi in veertig jaar Vlaamse geschreven pers (1966-2005) - Vantilt, Maarten (Leuven : KU Leuven, 2006)
Fonds Suzan Daniel (FSD)
Licentiaatsverhandeling K.U.Leuven
Nederlands
Thesis